THE INFLUENCE OF THE ENVIRONMENT ON THE BEARING STRUCTURES OF PASSENGER CARS (Transport systems and technologies, 2022)
The article analyzes the impact of the environment on the load-bearing metal structures of passenger cars using the example of special-purpose cars based on the results of technical diagnostics in order to extend the service life.According to the results of the analysis, it was determined that despite the initial high characteristics of the load-bearing elements and the body shell, the very design of the passenger car body creates favorable conditions for the development of corrosion of the internal surfaces of the load-bearing elements. The analysis of the obtained results showed that the main operational damage to body elements can be divided into mechanical and corrosion. despite the initial high characteristics of the load-bearing elements of the structure and the shell of the body, the very design of the body of the passenger car creates favorable conditions for the development of the process of corrosion of the internal surfaces of the loadbearing elements. The bodies of wagons built in 1982-1990, which came for repair from most railways, were examined. For a long time, the author analyzed the technical condition of the bodies of passenger cars, technical diagnostics in order to extend the service life. Corrosion damage to the body of the passenger car was detected: the floor of the body, the belt of the lower lining, through-corrosion of the lining of the side walls). It was established that the rate of corrosion destruction increases from zero in the initial period of operation, when the protective properties of the anti-corrosion coating are effective, to 0,8 mm per year. Such a high intensity is explained by the specifics of the body design and the conditions of its operation.
Keywords: special purpose wagon, load-bearing structures, corrosion, environment, damage.